Evidence on consumers' perceptions, understanding and uses of the Nutri-Score to improve communication about its update: a qualitative study with shopping observations in France - Marianne Cerf; Anne-Juliette Serry; Lucile Marty; Sophie Nicklaus; Pauline Ducrot (BMC, 2024)
Abstract Background The Nutri-Score is a front-of-pack nutrition label widely used in several European countries to improve the overall quality of consumers' diets. In the view of the upcoming update of the Nutri-Score algorithm, this study evaluates consumers' perceptions, understanding and uses of this label as well as their expectations or criticisms and opinions regarding the algorithm update. Methods Two complementary qualitative approaches were used in 2023. Six focus group discussions with a total of 51 participants as well as 20 individual shopping observations with real purchase conditions followed by in-depth interviews were conducted among French adults. The sessions were recorded, transcribed and then analysed using a thematic approach. Results Participants were familiar with the Nutri-Score but used it for food purchasing in a secondary way due to other more important criteria such as price or habits. They were aware that the label aimed to help them choose healthier products and to protect consumers. However, the lack of awareness about some aspects of the label such as the entity responsible for it or the calculation method of the score created a sense of mistrust about the Nutri-Score. Nevertheless, consumers did not report hearing criticism about the label in the media. Finally, they considered the updating of the label to be relevant. Conclusions Participants had a rather positive image of the Nutri-Score and its forthcoming update. Notwithstanding, to improve consumers' trust in the label, this study recommends launching an information campaign to explain its calculation method and reassure them that the Nutri-Score is a government-endorsed scheme as part of the national public health nutrition policy.